1999
DOI: 10.1111/j.1751-0813.1999.tb12085.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunophenotypic and histological characterisation of 109 cases of feline lymphosarcoma

Abstract: Objective To determine and analyse the immunophenotype and histological appearance of naturally occurring cases of lymphosarcoma in Australian cats. Design A prospective multi‐institutional study of naturally occurring feline lymphosarcoma. Methods One hundred and eighteen cats were referred for diagnosis and/or management of suspected lymphosarcoma. Tissue samples for histopathological analysis and immunophenotyping were collected as biopsies or at necropsy from 109 cases. Histological classification of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

13
88
1
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(104 citation statements)
references
References 18 publications
13
88
1
1
Order By: Relevance
“…This was a converse result to a previous study in Australia [9], and it might be due to variation depending on the geographical distribution. Also, a high incidence of alimentary lymphoma and high prevalence of T-cell lymphoma in the alimentary form led to the present result.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…This was a converse result to a previous study in Australia [9], and it might be due to variation depending on the geographical distribution. Also, a high incidence of alimentary lymphoma and high prevalence of T-cell lymphoma in the alimentary form led to the present result.…”
Section: Discussionsupporting
confidence: 70%
“…In alimentary lymphoma, while the ratio of T-and B-cell phenotypes varied in previous studies [16,25,27], a high incidence of T-cell subtype was observed in the present study. In mediastinal lymphoma, the B-cell subtype was found up to 1/3 of mediastinal cases in the present study, although there was a report about significant correlation with the T-cell phenotype [9]. Meanwhile, most of the nasal lymphomas were reported to be the B-cell subtype [4,13], and similar prevalence was observed here.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…The selection of 2 B-cell markers and 1 T-cell marker for phenotyping in this study was predicated on a 1999 study 11 in which CD79a was not expressed by 7% of the tumors that, based on other criteria, were concluded to be of B-cell type. These investigators also used 2 T-cell markers (CD5 and CD3) but reported that CD3 was sufficient to detect all of the T-cell tumors in their study.…”
mentioning
confidence: 99%
“…; Lozano-Alarcó n et al, 1992), cattle (Bos Taurus; Sasaki et al, 1997), cats (Felis catus; Gabor et al, 1999), and dogs (Canis lupus familiaris; Ponce et al, 2010). The multicentric form is the most common type of animal lymphoma and is seen in two-thirds of swine lymphomas (Jacobs et al, 2002).…”
mentioning
confidence: 99%